Correction of Darwin’s Tubercle with Plasma Exeresis - Roberto Valeriani, MD; Guido Firmani, MD; Maurizio Valeriani, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Summary:. Darwin’s tubercle (DT) is a congenital outer ear deformity characterized by a posterior thickening of the auricular helix. It is particularly common in certain ethnic groups, with reports ranging between 10% and 58% of the specific populations. Despite being common, this vestigial trait is poorly known. It carries no clinical significance, except in the cases where it might be hypertrophic, potentially causing psychological distress and significant social impairment. DT has been traditionally treated with surgical resections where part of the helical cartilage is removed. More recently, cartilage reshaping has been envisioned without cutting, suturing, or scars, using laser irradiation. Surgical resection, laser ablation and plasma exeresis are different tools in the surgeon’s armamentarium which may all be used successfully. Nevertheless, the first may cause noticeable scarring while the second may cause relevant laser-related complications. We present a noninvasive aesthetic medicine procedure based on plasma exeresis, which combines the benefits of a noninvasive procedure with the advantage of not requiring lasers for the correction of this cartilage defect. We present the case of a 28-year-old woman with right-sided hypertrophic DT, who requested a correction of the outer ear deformity. Two sessions were required, pain intensity during treatment was low, no complications were reported, and the patient was satisfied with the result at 6 months from the last session. Although plasma exeresis has been described in the past for several other non-invasive procedures of the skin, this is the first report of its kind for the correction of minor cartilage reshaping.